RESISTENSI PEMBERITAAN KOMUNITAS KONDE MEDIA PEREMPUAN INDONESIA TENTANG ISU-ISU GENDER DI MEDIA SOSIAL - M. Rayhan Hanif; Pingkan Dwi Lestari; Sri Yuniati (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2024)
This study aims to determine the resistance of the Indonesian Women's Media Konde Community's reporting on Gender Issues in Cyber Attack Cases. The research method used is qualitative research. Data collection was conducted using interview and documentation techniques. The data collected was then analyzed using qualitative descriptive analysis techniques. The results showed that the reporting of gender issues by the Konde Media Perempuan Indonesia community through social media caused resistance in the community. This is characterized by cyber attacks on the social media of the Konde Media Perempuan Indonesia community. The attack is a representation of patriarchal culture and masculinity that is still deeply rooted in society. Patriarchal culture in the real world is manifested in the use of new media. From the perspective of the concept of cyberfeminism, new media is the right tool to voice women's rights. However, the assumption of cyberfeminism is still not proven, one of which is due to the case of cyber attacks on the social media page of Konde Media Perempuan Indonesia. The hacking is a form of resistance to women's issues voiced by Konde in the new media.